2019
DOI: 10.1016/j.neuroscience.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptor Activation Directly Modulates Intrinsically Photosensitive Retinal Ganglion Cells

Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) encode light intensity and trigger reflexive responses to changes in environmental illumination. In addition to functioning as photoreceptors, ipRGCs are post-synaptic neurons in the inner retina, and there is increasing evidence that their output can be influenced by retinal neuromodulators. Here we show that opioids can modulate light-evoked ipRGC signaling, and we demonstrate that the M1, M2 and M3 types of ipRGCs are immunoreactive for μ-opioid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 85 publications
2
34
0
Order By: Relevance
“…The dark-adapted PLRs of MKO, McKO, and WT control mice were not significantly different; this may be due to compensatory mechanisms developed in the knockout mice from birth. CTAP’s enhancement of the rod/cone-driven PLR in the dark-adapted retina and melanopsin-driven PLR under photopic conditions in WT mice is consistent with our prior finding that the MOR-selective antagonist CTOP both recovered and increased the intrinsic light responses compared to control of rat ipRGCs recorded on multielectrode array (MEA) [ 33 ]. Thus, the intraocular application of CTAP appears to mimic the loss of in-circuit opioid effects achieved via knockout of MORs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The dark-adapted PLRs of MKO, McKO, and WT control mice were not significantly different; this may be due to compensatory mechanisms developed in the knockout mice from birth. CTAP’s enhancement of the rod/cone-driven PLR in the dark-adapted retina and melanopsin-driven PLR under photopic conditions in WT mice is consistent with our prior finding that the MOR-selective antagonist CTOP both recovered and increased the intrinsic light responses compared to control of rat ipRGCs recorded on multielectrode array (MEA) [ 33 ]. Thus, the intraocular application of CTAP appears to mimic the loss of in-circuit opioid effects achieved via knockout of MORs.…”
Section: Discussionsupporting
confidence: 90%
“…As previously mentioned, synaptic inputs onto ipRGCs downstream of rods and cones, including ON/OFF bipolar cells and amacrine cells, have been shown to extend the dynamic range of ipRGCs in both the intensity and temporal frequency domains [ 40 ]. Given that our prior work showed that MOR action in ipRGCs reduces excitability without affecting phototransduction [ 33 ], DAMGO is expected to reduce ipRGC signaling both when driven by rod/cone inputs and by the intrinsic melanopsin phototransduction pathway under bright light conditions. The greater pupillary constriction in the MKO group vs. the McKO group suggests that in the McKO group, in which MORs are absent from ipRGCs alone, opioids may be exerting inhibitory effects on elements of the retinal circuit downstream of the rod-cone photoreceptors [ 41 ], which are relevant for the integrated rod–cone and melanopsin-mediated PLR in response to bright blue irradiance [ 28 ], or alternatively, there may be centrally mediated endogenous opioid effects that are absent in MKO animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mu opioid receptor gene Oprm1 is differentially expressed in ipRGCs; it could regulate their light responses interacting with L-type calcium channels, which carry the majority of light-evoked inward calcium current in ipRGCs (Moises et al, 1994; Diaz et al, 1995; Doğrul et al, 2001; Hartwick et al, 2007). Recently, μ-opioid receptors (MORs) immunoreactivity was identified on rodent M1–M3 ipRGCs and MOR activation reduced ipRGC excitability via modulation of voltage-gated potassium and calcium currents (Cleymaet et al, 2019). Our data appear at odds with earlier reports that M1 and M4 ipRGCs express the melatonin receptor genes Mtnr1a and Mtnr1b (Sengupta et al, 2011; Pack et al, 2015; Sheng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%